2001
DOI: 10.1103/physreve.63.041111
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamically self-consistent theory for the Blume-Capel model

Abstract: We use a self-consistent Ornstein-Zernike approximation to study the Blume-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 37 publications
5
27
0
Order By: Relevance
“…II, we located [36] the tricritical point as K t = 0.7133͑1͒ and D t = 2.0313͑4͒; the expectation value of the tricritical vacancy density is vt = 0.6485͑2͒, rather close to the mean-field value 2 / 3. Consistency between these results and existing determinations [37,38], K t = 0.706͑3͒ , D t = 2.01͑1͒, and vt = 0.655͑6͒, exists within a margin of about twice the quoted errors. Here, we have applied other techniques, including a simultaneous analysis of various quantities for different systems such that parameters in common appear only once [16]; the details of these numerical analyses will be presented elsewhere [36].…”
Section: A Unconstrained Bc Modelssupporting
confidence: 85%
See 1 more Smart Citation
“…II, we located [36] the tricritical point as K t = 0.7133͑1͒ and D t = 2.0313͑4͒; the expectation value of the tricritical vacancy density is vt = 0.6485͑2͒, rather close to the mean-field value 2 / 3. Consistency between these results and existing determinations [37,38], K t = 0.706͑3͒ , D t = 2.01͑1͒, and vt = 0.655͑6͒, exists within a margin of about twice the quoted errors. Here, we have applied other techniques, including a simultaneous analysis of various quantities for different systems such that parameters in common appear only once [16]; the details of these numerical analyses will be presented elsewhere [36].…”
Section: A Unconstrained Bc Modelssupporting
confidence: 85%
“…The tricritical BC model (1) has been investigated on several three-dimensional lattices, and various techniques have been developed, including the self-consistent OrnsteinZernike approximation [37] and Monte Carlo simulations [36,38].…”
Section: A Unconstrained Bc Modelsmentioning
confidence: 99%
“…The vacancy density v at the tricritical point is v = vt = 0.6485͑2͒ [39]. These results are consistent with estimations [40,41] from other sources K t = 0.706͑4͒, D t = 2.12͑6͒, and vt = 0.652͑6͒, within two times the error margins as quoted between parentheses.…”
Section: Monte Carlo Methods and Sampled Quantitiessupporting
confidence: 90%
“…Figure 1 shows the phase diagram, in the -T plane, of the Blume-Capel model obtained by integration of HRT equations ͑temperatures are measured in unit of 6J/k B ). For comparison, results from SCOZA of Grollau et al ͓14,23͔ are also shown. The line of critical points ͑Néel line͒ ends at a tricritical point localized at T t ϭ0.230Ϯ0.002, c ϳ0.350Ϯ0.005.…”
Section: Resultsmentioning
confidence: 99%